O-GlcNAcylation regulates extracellular signal-regulated kinase (ERK) activation in Alzheimer’s disease - Ephrame, Sophiya John; Cork, Gentry K.; Marshall, Victoria; Johnston, Margaret A.; Shawa, Jenna; Alghusen, Ibtihal; Qiang, Amy; Denson, Aspin R.; Carman, Marisa S.; Fedosyuk, Halyna; Swerdlow, Russell H.; Slawson, Chad (Frontiers in Aging Neuroscience, 2023)
Introduction Aberrant activation of Extracellular Signal-Regulated Kinase (ERK) signaling is associated with Alzheimer’s disease (AD) pathogenesis. For example, enhanced ERK signal activation mediated by Apolipoprotein E4 (APOE4), which is a critical genetic risk factor for AD, increases the transcription of amyloid precursor protein (APP). We hypothesize that O-linked N-acetylglucosamine (O-GlcNAc) regulates the phosphorylation and activation of ERK. O-GlcNAc is a single sugar post-translational modification that dynamically cycles on and off proteins in response to nutrient changes by the action of the enzymes O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), respectively. However, O-GlcNAc quickly returns to a baseline level after stimulus removal (called O-GlcNAc homeostasis). Methods We did a serum reactivation time-course followed by western blot in SH-SY5Y neuroblastoma cells after long-term O-GlcNAcase (OGA) inhibition by Thiamet-G (TMG) treatment, O-GlcNAc transferase (OGT) knock-down (KD) and OGA KD. Brain tissues of C57BL6/J mice and 5XFAD Alzheimer’s disease mice intra-peritoneally injected with TMG for 1 month and C57BL6/J mice intra-peritoneally injected with TMG for 6 months were also used for western blot. Results We found that ERK1/2 phosphorylation at Thr 202/Tyr204 and Thr183/Tyr185 (p-ERK) are amplified and hence ERK1/2 are activated after long-term OGA inhibition in SH-SY5Y cells. In addition to pharmacological treatment, genetic disruption of O-GlcNAc by OGT KD and OGA KD also increased p-ERK in SH-SY5Y cells suggesting O-GlcNAc homeostasis controls ERK signaling. To determine how O-GlcNAc regulates p-ERK, we probed the expression of phosphorylated mitogen-activated protein kinase-kinase (p-MEK) which phosphorylates and activates ERK and Dual specificity phosphatase-4 (DUSP4) which dephosphorylates and inactivates ERK in SH-SY5Y cells. p-MEK increases in TMG treated and OGT KD cells whereas total DUSP4 decreases in OGT KD and OGA KD cells with serum reactivation time course. Next, we probed the role of OGA inhibition in regulating ERK activation using mice brain-tissue samples. Interestingly, 6-month intra-peritoneal TMG injection in C57BL/6J mice showed an increase in amplitude of p-ERK and APP protein levels, indicating long-term OGA inhibition potentially contributes to AD progression. Furthermore, 1-month TMG injection was sufficient to increase the amplitude of p-ERK in 5XFAD AD mice brains suggesting AD phenotype contributes to the acceleration of ERK activation mediated by OGA inhibition. Conclusion Together, these results indicate that disruptions to O-GlcNAc homeostasis amplify ERK signal activation in AD.